Development and validation of IHS4‐55, an IHS4 dichotomous outcome to assess treatment effect for hidradenitis suppurativa. (19th October 2022) - Tzellos, Thrasivoulos; van Straalen, Kelsey R.; Kyrgidis, Athanassios; Alavi, Afsaneh; Goldfarb, Noah; Gulliver, Wayne; Jemec, Gregor B. E.; Lowes, Michelle A.; Marzano, Angelo Valerio; Prens, Errol P.; Sayed, Christopher J.; van der Zee, Hessel H.; et al.
Abstract: Background: Validated, inclusive and easy‐to‐use outcomes for hidradenitis suppurativa are essential both in the clinical trial setting and clinical practice. The continuous IHS4 is a validated tool that dynamically assesses nodules/abscesses/draining tunnels and classifies disease severity as mild/moderate/severe. However, dichotomous outcomes are often required for clinical trials reporting. Objective: To develop and validate a dichotomous outcome based on IHS4 that can be used in clinical trial settings and day‐to‐day clinical practice. Methods: De‐identified data from the PIONEER‐I and ‐II studies were accessed through Vivli. Potential IHS4 thresholds were analysed using baseline to Week 12 data from adalimumab‐ and placebo‐treated hidradenitis suppurativa patients in the PIONEER‐I trial. The final threshold was chosen based on its ability to discriminate between patients treated with adalimumab or placebo and its association with reduction in inflammatory lesions. The final threshold was validated using data from baseline to Week 12 from adalimumab‐ and placebo‐treated hidradenitis suppurativa patients in both the PIONEER‐II and the combined PIONEER‐I and ‐II studies. Results: The best performing cut‐off for the IHS4 was a 55% reduction of the IHS4 score (IHS4‐55). Patients who achieved the IHS4‐55 had an odd's ratio of 2.00 [95%‐CI 1.26–3.18, p  = 0.003], 2.79 (95%‐CI 1.76–4.43, p  < 0.001) and 2.16 (95%‐CI 1.43–3.29, p  < 0.001) for being treated with adalimumab rather than placebo in PIONEER‐I, PIONEER‐II and the combined dataset, respectively. Additionally, the achievement of the IHS4‐55 was associated with a significant reduction in inflammatory nodules, abscesses and draining tunnels in all analysed datasets. Conclusions: IHS4‐55,  a novel dichotomous IHS4 version, based on a 55% reduction of the total score was developed. The IHS4‐55 performs similarly to the HiSCR in discriminating between adalimumab‐ and placebo‐treated hidradenitis suppurativa patients and shows significant associations with reductions in lesion counts. Moreover, the IHS4‐55 addresses some of the HiSCR drawbacks by dynamically including draining tunnels in a validated manner. By allowing the analysis of hidradenitis suppurativa patients with an abscess and nodule count below 3 but many draining tunnels, this outcome measure will improve inclusivity in clinical trials.